The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-13574-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid polymorphism in chloroplast thylakoid membranes – as revealed by 31P-NMR and time-resolved merocyanine fluorescence spectroscopy

Abstract: Chloroplast thylakoid membranes contain virtually all components of the energy-converting photosynthetic machinery. Their energized state, driving ATP synthesis, is enabled by the bilayer organization of the membrane. However, their most abundant lipid species is a non-bilayer-forming lipid, monogalactosyl-diacylglycerol; the role of lipid polymorphism in these membranes is poorly understood. Earlier 31P-NMR experiments revealed the coexistence of a bilayer and a non-bilayer, isotropic lipid phase in spinach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 80 publications
12
58
0
Order By: Relevance
“…OJIP transients also showed very characteristic changes, with a clear trend, increasing most prominently the initial rise, the O‐J phase, with increasing time of thylakoid membrane storage. In agreement with our earlier measurements (Garab et al ), the F v / F m ratio decreased only slightly and gradually, from 0.765 ± 0.025 (0 h) to 0.754 ± 0.027 (6 h) and to 0.740 ± 0.031 (8 h); also, the dependence of the F 0 as a function of the storage time showed no significant variation (data not shown). It is also noteworthy that storage exerted no discernible effect on the rise kinetics recorded in the presence of DCMU (Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…OJIP transients also showed very characteristic changes, with a clear trend, increasing most prominently the initial rise, the O‐J phase, with increasing time of thylakoid membrane storage. In agreement with our earlier measurements (Garab et al ), the F v / F m ratio decreased only slightly and gradually, from 0.765 ± 0.025 (0 h) to 0.754 ± 0.027 (6 h) and to 0.740 ± 0.031 (8 h); also, the dependence of the F 0 as a function of the storage time showed no significant variation (data not shown). It is also noteworthy that storage exerted no discernible effect on the rise kinetics recorded in the presence of DCMU (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Instability of the lipid‐phase behaviour of thylakoid membranes has already been indicated by the strong temperature dependence of the 31 P‐NMR spectra of thylakoids (Krumova et al ): with the gradual increase of the temperature, between 7 and 28°C, the intensity of the bilayer‐phase resonances gradually diminished and disappeared, while the isotropic peak increased. In our earlier study (Garab et al ), we have observed a similar instability of the bilayer phase and the increase of the isotropic phase(s) during the storage of membranes in the dark at 5°C. These variations could not be correlated with similar changes in the basic structural and functional parameters of the thylakoid membranes, tested by CD and 77 K fluorescence spectroscopy and Chl a fluorescence of PSII, the F v / F m , ratio.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations